Low-dose methamphetamine addiction induced opioid receptor sensitization in polydrug-dependent mice - Ridzwan, Irna Elina; Suhaimi, Maryam Saadah; Muhamad, Abdul Halim; Kasmuri, Abdul Razak; Mohamed Nazar, Nor Ilyani; Hashim, Ridzwan; Syd Mohmad Faudzi, Syed Mohd Syahmi (Springer, 2018)
Polydrug dependence shows an increasing trend in prevalence among addicts. It is a result of an addict abusing another drug to mask the undesirable effects of another drug. However, this could lead to adverse neuroadaptations. Therefore, we aim to investigate the effects of low-dose methamphetamine use in morphine-dependent subjects during reinstatement following treatment (0.3 mg/kg buprenorphine / 1.0 mg/kg naltrexone combination) in mice. Using tail-withdrawal assay, the involvement of opioid receptors was investigated at 1.0-5.0 mg/kg methamphetamine, i.p. at 52°C. The results showed that analgesic activity was only detected at the highest dose given which was successfully blocked with 1.0 mg/kg naltrexone, i.p. (p<0.001, n=6). Next, naive mice were randomly divided into three groups (n=at least 12), where the mice were made dependent (p<0.01) to morphine (7.5 mg/kg, i.p.), methamphetamine (1.0 mg/kg, i.p) or morphine/methamphetamine combination (7.5 mg/kg and 1.0 mg/kg respectively). Although relapse was successfully attenuated with non-significant difference compared to baseline, it was found that 6 (out of 13) mice showed sign of opioid receptor sensitization through stereotype and Straub's tail response (>45°) which was not detected in the morphine-, methamphetamine-dependent groups and during pre-screening of treatment drug. This suggest that although methamphetamine has little apparent withdrawal symptoms, it has the ability to sensitize the opioid receptors even at 'inactive' dose when it is used concurrently with morphine.